Impact of Visual Aid in Creating Awareness about Sustainable Tourism in School Students - Agrawal, Shreenabh (JOURNAL OF INDIAN EDUCATION, 2019)
Picnics, trips and excursions are a common practice in almost all schools of Nagpur. Thus, picnics of school students become a very important tourist segment of our country which can be systematically trained for sustainable tourism and guided during travel by the teacher leader. There is a need to create awareness about sustainable tourism in schools. The present research focuses on using visual aid as a pedagogical tool to enhance awareness about sustainable tourism in school students. For this, it was necessary to find the motivation of schools in their choice of travel destinations and to check the level of importance given to sustainable tourism while deciding the destination. The next objective was to understand the level of awareness regarding sustainable tourism in teachers, parents and students. The research was aimed at educating the parents, teachers and students such that their perspective of school tourism changes by way of a visual aid created by the researcher in the form of a video. In this research project, a pre-post impact analysis of a video created by the researcher explaining sustainable tourism was tested on parents, teachers and students from various schools in Nagpur. A survey of 150 participants including school teachers, parents and students was conducted in two phases, once before the experiment and the second after the experiment. The experiment constituted the video screening. The observations of both phases were recorded. Statistical analysis of the data was carried out by applying A Class student writing a paper with this extensive research and it was found that visual aid had a significant effect on enhancing the awareness level of sustainable tourism.